SUFISM IN ISLAM - Abdul Wahab Syakhrani; M. Ibnu Rabi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
Sufism is an effort to get closer to God as closely as possible, even to unite oneself with God, through the path of spiritual cleansing from reprehensible qualities. Starting from an effort like this, the mutashawwifin scholars then made staging formulations (maqamat, stations/stages) that must be passed by a seeker/salik in order to be able to unite with God. Therefore, in the tradition of Islamic Sufism, various Sufism theories developed, both moderate and extreme. The diversity of Sufism is increasing with the emergence of tarekat schools, which have their own methods and traditions.